Homology Model of a Catalytically Competent Bifunctional Rel Protein - Civera, Monica; Sattin, Sara (Frontiers in Molecular Biosciences, 2021)
Bacteria have developed different bet hedging strategies to survive hostile environments and stressful conditions with persistency being maybe the most elegant yet still poorly understood one. Persisters’ temporary tolerance to antibiotic treatment hints at their role not only in chronic and recurrent infections but also in the insurgence of resistant strains. Therefore, hampering persisters formation might represent an innovative strategy in the quest for new effective antimicrobial compounds. Among the molecular mechanisms postulated for the persister phenotypic switch, we decided to focus our attention on the stringent response and, in particular, on the upstream triggering step that is the accumulation of guanosine tetra- and pentaphosphate, collectivity called (p)ppGpp. Intracellular levels of (p)ppGpp are regulated by a superfamily of enzymes called RSH (RelA/SpoT homologue) that are able to promote its synthesis via pyrophosphate transfer from an ATP molecule to the 3’ position of either GDP or GTP. These enzymes are classified based on the structural domain(s) present (only synthetase, only hydrolase, or both). Here we present our work on RelSeq (from S. equisimilis), still the only bifunctional Rel protein for which a GDP-bound “synthetase-ON” structure is available. Analysis of the synthetase site, occupied only by GDP, revealed a partially active state, where the supposed ATP binding region is not conformationally apt to accommodate it. In order to achieve a protein model that gets closer to a fully active state, we generated a chimera structure of RelSeq by homology modelling, starting from the crystal structure of the catalytically competent state of RelP, a smaller –single domain– Rel protein from S. aureus. Molecular dynamics (MD) simulations allowed verifying the stability of the generated chimera model. Virtual screening and ligand design studies are underway.